Training received, knowledge, and use of Silver Diamine Fluoride among Italian dentists: a nationwide survey - Claudia Salerno; Giulio Conti; Silvia Cirio; Cinzia Maspero; Andrea Senna; Guglielmo Campus; Maria Grazia Cagetti (BMC Oral Health)
Abstract Objective To investigate the education, knowledge and behaviour of Italian dentists regarding Silver Diamine Fluoride (SDF). Methods A cross-sectional study was conducted from January to December 2022, through an online survey linked to an online continuing medical education (CME) course sent to Italian dentists. A priori power analysis estimated the necessary sample to be 1480 dentists with an anticipated frequency of 50% and a power of 99.99%. The questionnaire included 46 questions on participants ‘ demographic characteristics, training received, clinical knowledge of SDF, and attitudes and behaviours regarding its use. Descriptive statistics, bivariate, and mutlivariable regression analyses were performed to determine the association between the variables. Results The response rate was 6.1% with 3876 respondents, evenly distributed geographically. Less than 10% of respondents had received training at undergraduate, postgraduate or masters level. A minority of dentists were familiar with the use of SDF for the treatment of dentine hypersensitivity (19.0%) and for the treatment of caries in children (22.2%) and adults (15.7%). The percentage of dentists who reported SDF use at least once was 20.6%. On mutlivariable analysis (χ2 (11) = 995.9 p-value < 0.01), dentists who used SDF were positively associated with those who cared for patients with special needs, those who received good undergraduate or postgraduate training, and those who knew how to use SDF (p < 0.01). A second mutlivariable analysis (χ2 (11) = 47.9 p-value < 0.01) revealed that younger respondents were associated with good training and knowledge of the use of SDF received during undergraduate studies, while older respondents were associated with good training received on managing hypersensitivity and caries in adults (p < 0.01). Conclusions Overall, Italian dentists ‘ education, knowledge, and use of SDF were relatively poor. The majority of the sample ‘s responses were not consistent with scientific evidence. The use of SDF among Italian dentists is still far from being a reality. In Italy, it is necessary to increase training on SDF, primarily through the university, to hopefully increase its use, especially in non-invasive caries treatment.